4-(4-Hydroxymethyl-1H-1,2,3-triazol-1-yl)Benzoic Acid - Ishak, D.H.A.; Tajuddin, Hairul Anuar; Abdullah, Z.; Abd Halim, S.N.; Tiekink, E.R.T. (International Union of Crystallography, 2011)
In the title compound, C10H9N3O3, there is a small twist between the benzene and triazole rings dihedral angle = 6.32 (7)degrees; the carboxylic acid residue is almost coplanar with the benzene ring to which it is attached O-C-C-C torsion angle = 1.49 (19)degrees. The main deviation from coplanarity of the non-H atoms is found for the hydroxy group which is almost perpendicular to the remaining atoms N-C-C-O torsion angle = -75.46 (16)degrees. In the crystal, the presence of O-H center dot center dot center dot O (between carboxyl groups) and O-H center dot center dot center dot N (between the hydroxy group and the triazole ring) hydrogen bonds leads to supramolecular chains along 03 (1) over bar. The chains are connected into sheets via C-H center dot center dot center dot O(hydroxy) interactions.